The LKPD Design with the CIRC Type Cooperative Learning Model at MI Al Huda Banyuarang - Najiyah, Rika Rifatun; Rofi’ah, Siti (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
Student worksheets, which are usually called LKPD, are one of the teaching materials that can be arranged according to the needs of students. The LKPD used in MI Al-Huda Banyuarang was not able to facilitate group learning activities or discussions. Students find weather conditions material difficult because the images used are not concrete or unreal images so students find it difficult to distinguish. This study aims to produce LKPD based on cooperative learning type CIRC (Cooperative Integrate Reading Composition) on class III weather conditions using concrete or real pictures. This research was conducted to find out how the design process and analyze the feasibility test of students' worksheets at MI Al Huda Banyuarang. This research includes development research using the 4D model with the stages of Define, Design, Develop, and Disseminate. The results of the development are LKPD with a validation value of 98% from material experts, 90% from teaching material designs, and 92% from learning experts or class teachers at MI Al Huda Banyuarang. Of the three validators, they get an average score of 93.3% with very decent criteria.